Student-teachers’ Emotion Regulation in Speaking - Aloysia Berlindis Lasar (The Study Program of English Education of Palangka Raya University, 2024)
Several scholars in education have asserted that emotions play a significant role in motivation to learn. On the side of self-regulated learning theory, it is believed that a learner would succeed more if he owned fully constructed self-regulation in learning. This research aims to describe the student-teachers’ academic emotions, specifically in speaking, and later to elaborate on their tendency to regulate it. The researcher applied mixed methods in this study. The data was obtained through questionnaires and in-depth interviews. Supporting theory used to gain the description of the student-teacher state of academic emotion is the theory proposed by Pekrun et al. (2002). The result showed that the student-teachers tend to perceive negative emotions about their ability to speak. However, they managed to use a cognitive reappraisal strategy to modify their academic emotion in both stages of preparation and mastering speaking. Meanwhile, they tend to use expressive suppression to manage their academic emotion in performing speaking. Moreover, the implications and implementation of emotion regulation in the East Nusa Tenggara context as a part of the researcher’s reflection are also discussed.